2015
DOI: 10.1123/japa.2013-0142
|View full text |Cite
|
Sign up to set email alerts
|

Social Patterning in Grip Strength, Chair Rise, and Walk Speed in an Aging Population: The Czech HAPIEE Study

Abstract: Background:The aim was to examine the association of objective measures of physical functioning (PF) with education and material circumstances and the decline in PF with age by socioeconomic position (SEP). Methods: In 3,205 subjects (60-75 years) from the Czech Republic, we assessed relationship between PF, SEP, and age. Linear regression was used to assess PF measures and SEP measures. Results: Crosssectional decline in PF by age was similar in all individuals. Differences between SEP groups were similar acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Of course, there have been some recent studies based on longitudinal data. Specific analyses of the influencing factors of grip strength and muscle atrophy include (1) the impact of PA on grip strength (23,24); (2) the impact of SA on grip strength (17,25); (3) the influence of other individuals' heterogeneity on grip strength, the most important of which is age (26,27); and (4) the relationship between medical indicators and physiological mechanisms, including PA, nutrient intake (protein), oxidative stress, inflammation, and hormone changes, and more systematic therapeutic interventions (14). High levels of serum interleukin (IL)-6, C-reactive protein (CRP), and α1antichymotrypsin (ACT) are associated with decreased muscle strength or muscle mass (muscular sarcopenia) (28).…”
Section: Grip Strength As a Biomarker Of The Health Of Elderly Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…Of course, there have been some recent studies based on longitudinal data. Specific analyses of the influencing factors of grip strength and muscle atrophy include (1) the impact of PA on grip strength (23,24); (2) the impact of SA on grip strength (17,25); (3) the influence of other individuals' heterogeneity on grip strength, the most important of which is age (26,27); and (4) the relationship between medical indicators and physiological mechanisms, including PA, nutrient intake (protein), oxidative stress, inflammation, and hormone changes, and more systematic therapeutic interventions (14). High levels of serum interleukin (IL)-6, C-reactive protein (CRP), and α1antichymotrypsin (ACT) are associated with decreased muscle strength or muscle mass (muscular sarcopenia) (28).…”
Section: Grip Strength As a Biomarker Of The Health Of Elderly Peoplementioning
confidence: 99%
“…By analyzing health data for elderly Europeans, Jancova-Vseteckova et al (17) found that education, professional class, income, and wealth had a predictive effect on male grip strength, while only education and wealth had a predictive effect on female grip strength. However, they provided no further analysis of more complicated impact mechanisms; while they showed that wealth affected grip strength, there was no explanation for the effect.…”
Section: Wealthmentioning
confidence: 99%
See 1 more Smart Citation